EDUCATION AND OBESITY PREVENTION THROUGH HEALTHY LIFESTYLES - Prasiwi, Nikita; Tysa Runingsari (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: Obesity is one of the significant public health problems in Indonesia, with an increasing prevalence due to unhealthy diet, low physical activity, and hormonal factors. This disease increases the risk of degenerative diseases such as diabetes mellitus, hypertension, and cardiovascular disease. As a preventive measure, health education was held with the theme